Cervical spinal cord intramedullary abscess. Case report - (:unkn) unknown (My University, 2001)
A case of progressive symptoms and signs of cervical spinal cord damage due to intramedullary abscess is reported. The literature is reviewed and the radiological features, particularly magnetic resonance image, are analyzed.
Keywords: Female; Humans; Middle Aged; Laminectomy; Magnetic Resonance Imaging; Cervical Vertebrae; Spinal Cord Diseases; Abscess; Medulla Oblongata